Developing Speaking Skills in English among School Children Using Technology Support - Sultana, Yeasmin (JOURNAL OF INDIAN EDUCATION, 2015)
This paper is based on an experimental type of research work. It aimed to see the effectiveness of using technology support in classroom situation to develop speaking skills of learners studying in Class VI in a Bengali medium school in Malda district of West Bengal. The researcher used animated videos of Panchatantra tales as technology supportive materials in her study. The researcher had used two groups pre-test and post-test design and followed the purposive sampling method. Experimental and controlled groups were formed before giving them the treatment. The data were collected through administering various exercises and tasks requiring the learners to provide short answers, retelling a story, etc. The data were analysed quantitatively and qualitatively. The quantified data demonstrate that students from the experimental group did better than the controlled group in terms of development of speaking skills. Therefore, we can say that technology support rendered English language learning interesting and motivating.